Management of the Islamic Boarding School Maskanul Huffadz in Medan City in Managing Social Media as a Media for Da'wa - Zahrani Fadila; Azhar (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to examine the management of social media as a medium for da'wah carried out by Pesantren Maskanul Huffadz in Medan City. The pesantren Maskanul Huffadz in Medan City has utilized social media platforms such as Instagram and TikTok to convey and disseminate Islamic messages to a broad audience. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews, observations, and document studies. The research findings indicate that social media management at Pesantren Maskanul Huffadz in Medan City involves structured content planning, organized implementation, and periodic evaluation of the effectiveness of uploaded content. The da'wah strategy includes a creative approach through visual content, videos, and writings that are relevant to the audience's needs. The challenges faced include device limitations at Pesantren Maskanul Huffadz in Medan City. However, the pesantren has successfully built a positive image and expanded its da'wah reach through active interactions with social media followers. This study concludes that effective social media management can serve as a powerful tool in supporting da'wah activities. Pesantren Maskanul Huffadz in Medan City is expected to continue developing digital strategies to address the challenges of the information technology era.